Child maltreatment and mental health- Ayurveda perspective - Karuvanthodi, Preetha; M, Jithesh (Asian Journal of Pharmaceutical Research and Development, 2024)
Child maltreatment is a pervasive and complex societal issue that encompasses various forms of abuse and neglect, posing significant threats to the well-being and development of children worldwide. The World Health Organization (WHO) defines child maltreatment as “all forms of physical and emotional ill-treatment, sexual abuse, neglect, and exploitation that results in actual or potential harm to the child’s health, development or dignity.” Abuse of children can have serious short and long term effects on physical, sexual, and mental health. These include physical harm, such as concussions and severe disabilities, especially in young children, as well as anxiety, sadness, and post-traumatic stress disorder. Child abuse has a strong correlation with alcohol and drug usage and can impact cognitive and academic performance.Priority must be for protecting and preserving the safety of abused children. The goals of ongoing treatment are to lessen the long-term psychological and physical effects of abuse as well as preventing reoccurrence. Child maltreatment is a global concern with profound implications for the physical, emotional, and psychological well-being of children. While conventional approaches in the field of child protection have made significant strides, there is growing interest in exploring complementary practices, such as Ayurveda, to enhance the overall well-being of maltreated children. The potential role of Ayurveda in addressing child maltreatment, considering its ancient roots in promoting holistic health and balance is to be highlighted. Ayurveda also proposes the principles for taking care of childhood and preventing maltreatment for them. Therapies, including herbal remedies, massage, and meditation is having the potential in managing and rehabilitating the children affected by maltreatment. Ayurveda focuses in addressing not only physical symptoms but also mental and emotional aspects that aligns with the comprehensive needs of maltreated children.